Splashdance - Starin, Liz (New York : Farrar Straus Giroux, 2016)
"Ursula, a bear, and Ricardo, a human, are preparing for the water ballet competition. But a new regulation at the community pool--no bears--leaves Ursula cut from the contest. Luckily, she encounters a group of undaunted animal swimmers at a local pond, and Ursula and her new team figure out a way to participate in the competition and make sure everyone is welcome at the pool once and for all"--
Keywords: Bears -- Juvenile fiction; Swimming -- Juvenile fiction; Teamwork (Sports) -- Juvenile fiction; Toleration -- Juvenile fiction; Bears -- Fiction; Swimming -- Fiction; Teamwork (Sports) -- Fiction; Toleration -- Fiction